2016
DOI: 10.1007/s00520-016-3370-4
|View full text |Cite
|
Sign up to set email alerts
|

An audit of acute oncology services: patient experiences of admission procedures and staff utilisation of a new telephone triage system

Abstract: MethodsPatient views were elicited via a questionnaire and semi-structured interviews. The TT forms were analysed descriptively evaluating completion and data quality, reported symptoms and their severity; and advice given (including admission rates). ResultsPatients (n=40) reported high satisfaction with the new AOS. However, 56% of patients delayed 2 days or more before contacting the unit.In 2011, 26% of all admitted patients were triaged via the TT system; 133 TT forms were completed. In June 2013, 49% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 4 publications
(5 reference statements)
1
17
0
1
Order By: Relevance
“…Many patients however, delay seeking care especially out of hours [3, 5]. This concurs with the findings of a UK enquiry into patient outcome and death (National Confidential Enquiry into Patient Outcome and Death, NCEPOD) which found that of patients dying within 30 days of systemic cancer therapy, 17% delayed seeking advice for over 24 h [6].…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…Many patients however, delay seeking care especially out of hours [3, 5]. This concurs with the findings of a UK enquiry into patient outcome and death (National Confidential Enquiry into Patient Outcome and Death, NCEPOD) which found that of patients dying within 30 days of systemic cancer therapy, 17% delayed seeking advice for over 24 h [6].…”
Section: Introductionsupporting
confidence: 62%
“…Severe AEs can escalate to hospitalisation for potentially life-threatening toxicities: 18% of cancer patients present to emergency services within 14 days of a scheduled hospital visit for symptom management (infection, fever, nausea/vomiting, pain, breathlessness) [1–4]. Patients with breast, gastrointestinal, colorectal cancers and those with metastatic disease are amongst those most likely to have emergency admissions [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telephone communication is a unique opportunity to improve health care access, optimize patient coordination, and enhance the patient's experience outside the hospital setting. 12,23,24 During the day, our office RNs handle these calls and are continually coordinating patient care at all of the different sites we serve. After hours calls are handled by the physicians, APPs, and RNs who follow up with the office staff and communicate any issues that may have arisen overnight and need to be addressed.…”
Section: Outpatient Clinicmentioning
confidence: 99%
“…In this two-centre study, professional and patient care pathways and the role of eRAPID were explored via audit and interviews with staff, patients and relatives [ 49 – 51 ]. Additionally, we identified the AEs associated with urological, gastrointestinal and gynaecological cancers from patient interviews [ 50 ] and via systematic reviews of PRO reporting for these groups [ 52 54 ].…”
Section: Introductionmentioning
confidence: 99%